The behavior of sulphur forms of three lignites exposed to pyrolysis temperatures between 350 and 950 degrees C - (:unkn) unknown (ELSEVIER SCI LTD, 2004)
Three selected Turkish lignites were pyrolyzed at seven different temperatures between 350 and 950 degreesC for 7 min. The lignites and their chars were analyzed quantitatively for their total sulphur content and sulphur forms. The alkaline oxide contents of the lignites and selected char samples were deter-mined. Calcium compounds, which prevail in all of the parent lignites, undergo various chemical changes during pyrolysis. The results clearly indicate that both the temperature and the calcium oxide contents affect the behavior of various sulphur forms during pyrolysis. The organic sulphur decomposition and formation is the most difficult to predict. (C) 2003 Elsevier Ltd. All fights reserved.
Keywords: lignite; pyrolysis; sulphur forms; TURKISH LIGNITES; ORGANIC MATRIX; COAL PYROLYSIS; REMOVAL; PYRITE; DESULFURIZATION; HYDROPYROLYSIS; KINETICS